KARAKTERISTIK PEMENUHAN KEBUTUHAN SPIRITUALITAS PADA PASIEN YANG DIRAWAT DI RUANG ICU - Rasmita, Dina (Jurnal Keperawatan Priority, 2021)
Spirituality was important when an individual is sick. Patients ICU with spiritual distress, so they need to fulfill their spiritual needs. Fulfillment spirituality needs can be done by nurses and families. The purpose was to determine how nurses and patients’ families fulfilling the spiritual needs of ICU patients. This study was a descriptive design. Nurses who work in the Intensive Care Unit (ICU) and families of ICU patients were the populations of this study. The sample size was determined using a purposive sampling technique, which 30 ICU nurses and 32 ICU patient families. The data collection tool used a questionnaire. Data analysis used univariate analysis with frequency distribution. The results show that 66.7% of the nurses fulfilled the spiritual needs of patients with a good category, 53.1% of the patients’ families were a not good category in fulfilling ICU patient’s spiritual needs. This study concludes that the fulfillment of spirituality needs in ICU patients has been optimally implemented by nurses but has not been optimally implemented by the family. Fulfillment spirituality needs in ICU patients by nurses with good categories so nurses are improved it through training and nurses can increase the family role.